Strategi DASHAT-IPPE Untuk Mengatasi Stunting di DKI Jakarta - Nursamsiyah, Putri; Wava, Ainun; Muthi, Amirah Zahra; Setiawan, Cindyaningsih; Sani, Esya Fitria; Ali, Muhamad Khaedar; Yuliani, Shahibah (Indonesian Journal Publisher, 2024)
Jakarta as a metropolitan city still faces very complex problems, one of which is stunting. Stunting is a condition in which children experience stunted or stopped growth due to chronic malnutrition, usually occurring during early growth. The purpose of this study is to determine the picture of stunting in DKI Jakarta and reveal the DAHSAT-IPPE strategy to overcome stunting in DKI Jakarta. The research method used is a literature study, which synthesizes and analyzes data from various relevant sources. The results showed that there are factors and causes of stunting in Jakarta, such as parents' economic income, parents' education, parenting and nutrition, infant weight at birth, infant feeding and feeding schedules as well as parents' knowledge and behavior towards nutrition. Therefore, strategies that can be done to overcome stunting are DAHSAT (Healthy Kitchen to Overcome Stunting), Immunization, Nutrition Action Program (ABG), Supplementary Feeding (PMT) and Clean Water and Healthy Latrine (ABS) Education.